The world is flat a brief history of the twenty-first century - Friedman, Thomas L. (Penguin Books, 2006)
This text presents a picture of the state of globalisation, its successes and discontents, in the 21st century. The author demystifies the brave new world for readers, allowing them to make sense of the often bewildering global scene unfolding before their eyes